2022
DOI: 10.1530/joe-21-0209
|View full text |Cite
|
Sign up to set email alerts
|

Effects of PD-1 blockade on ovarian follicles in a prepubertal female mouse

Abstract: Immunotherapy has emerged at the forefront of cancer treatment. Checkpoint inhibitor pembrolizumab (KEYTRUDA), a chimeric antibody which targets programmed cell death protein 1 (PD-1), has been approved by the FDA for use in pediatric patients with relapsed or refractory classical Hodgkin’s lymphoma. However, there is currently no published data regarding the effects of pembrolizumab on the ovary of female pediatric patients. In this study, prepubertal immunocompetent and immunodeficient female mice were injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…We show herein that membrane bound and soluble PD‐1 pathway receptor and ligand proteins are expressed in resident (non‐lymphoid/non‐myeloid) cells of the human ovary, and can be found in the fluid collected from peri‐ovulatory follicles during IVF retrieval procedures. These data are reminiscent of one of our group's prior findings evaluating PD‐1 pathway expression and function in a mouse model where follicle numbers were evaluated after antibody (pembrolizumab) PD‐1 blockade 29 …”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…We show herein that membrane bound and soluble PD‐1 pathway receptor and ligand proteins are expressed in resident (non‐lymphoid/non‐myeloid) cells of the human ovary, and can be found in the fluid collected from peri‐ovulatory follicles during IVF retrieval procedures. These data are reminiscent of one of our group's prior findings evaluating PD‐1 pathway expression and function in a mouse model where follicle numbers were evaluated after antibody (pembrolizumab) PD‐1 blockade 29 …”
Section: Discussionmentioning
confidence: 69%
“…32,39,40 STIC cells detach from the tubal lumen and engraft at distant sites within the peritoneum, including the surface of the ovary at ovulation site(s). 41,42 During a preliminary evaluation of Pd-1 pathway protein expression in the mouse ovary, we detected broad expression of the receptor and ligands in the organ, in somatic immune and non-immune cells and oocytes (consistent with 29 ). There was also an existing report in a publicly-available large-scale gene expression screen (LifeMap Discovery) that showed that PD-1 pathway transcripts are detectable in human cumulus granulosa cells (HCGC).…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…A 2021 study of checkpoint inhibitor pembrolizumab in a prepubertal mouse model found that PD-1 checkpoint blockade affects the ovarian reserve through a mechanism possibly involving inflammation-mediated follicle depletion. In contrast to IO, PDL-1 expression, the target antigen of pembrolizumab, was demonstrated in the murine ovary [ 20 ]. These findings support the role of either a direct effect of anti-PDL-1 treatment or resultant inflammatory responses on ovarian function.…”
Section: Discussionmentioning
confidence: 99%